Screening of microbiological element of three fish pond in Terachi, Kuala Pilah, Negeri Sembilan / Nur Jihan Jasni - Jasni, Nur Jihan (2017)
The screening of microbiological element of fish ponds is vital in aquaculture as the information provided can indicate if any potential hazard can affect the fish cultured or human. This study aims to isolate and identify bacteria from three different fish pond at Terachi, Kuala Pilah and to evaluate the bacteriological profile of those ponds. The bacteria isolated from those fish ponds using spread plate method and streak plate method were subjected to gram stain and biochemical tests for further identification and characterization. Based on the results, the total coliform count was the highest in Kolam Ikan Talapia (P1) which is 3.35 × 102 cfu/mL. The bacterial strain successfully isolated and identified fromthe ponds were Bacillus spp., Escherichia coli, Klebsiella spp., Pseudomonas spp., Salmonella spp. and Staphylococcus spp. The study show that the ponds were contaminated with pathogenic bacteria that can be risky to fish and to human health thus causing diseases.